2009
DOI: 10.1080/10428190802663205
|View full text |Cite
|
Sign up to set email alerts
|

How much does it cost to treat children with Hodgkin lymphoma in Africa?

Abstract: Hodgkin lymphoma (HL) is a common B-cell childhood neoplasm and it has a higher incidence in the 0-14 year age group in developing countries compared to developed countries. Treatment achieves a cure rate of about 80%. In African countries with a small gross domestic product per capita the cost of treating HL in children may be prohibitive. To determine the direct costs of treatment of HL in South Africa and to propose a more cost-effective approach to investigation and treatment for children diagnosed with HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 9 publications
1
24
2
Order By: Relevance
“…As in other developing countries, the 6-14 years age group was most affected by Hodgkin lymphoma [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…As in other developing countries, the 6-14 years age group was most affected by Hodgkin lymphoma [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…As in other developing countries, the 6–14 years age group is most affected by Hodgkin lymphoma [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, a series of clinical trials reported equal efficacy but better tolerability for ABVD in comparison to MOPP-ABVD [44][45][46][47]. Due to its safety in the outpatient setting, even in developing countries without specialized inpatient care [48], ABVD has become widely accepted as standard regimen for advanced HL. Various alternating or hybrid regimens were subsequently investigated to improve the longterm failure-free survival (FFS) of 47 % and OS of 59 % in patients treated with ABVD [49].…”
Section: Advanced-stage Hlmentioning
confidence: 98%